2010
DOI: 10.2164/jandrol.108.007054
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Rat Testis and Epididymis Under Intermittent Hypobaric Hypoxia: Protective Role of Ascorbate Supplementation

Abstract: Hypobaric hypoxia (HH), an environmental condition of high altitude encountered by mountaineers, miners, and observatory, rural health, border patrol, and rural education workers, jeopardizes normal physiologic functions in humans. The present study was conducted to evaluate the effects of intermittent HH (IHH; equivalent to 4600 m above mean sea level) on oxidative stress and the protective role of dietary ascorbic acid on rat testis and epididymis. Ten-week-old male Wistar rats were assigned to 1 of 6 groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 34 publications
0
49
0
1
Order By: Relevance
“…Recent studies reinforce the existence of an increased oxidative metabolism in rat epididymis subjected to ICH [45,46]. Hence, an increased production of ROS gives way to a rise in apoptosis at the germinal cell level, leading to a state of hypospermatogenesis [46,47].…”
Section: Reproductive Responses and Treatmentmentioning
confidence: 75%
See 1 more Smart Citation
“…Recent studies reinforce the existence of an increased oxidative metabolism in rat epididymis subjected to ICH [45,46]. Hence, an increased production of ROS gives way to a rise in apoptosis at the germinal cell level, leading to a state of hypospermatogenesis [46,47].…”
Section: Reproductive Responses and Treatmentmentioning
confidence: 75%
“…One potential alternative is to incorporate food with high antioxidant levels to the diet in those people exposed to HA, and we have shown that this may have a positive effect in the protection of cells facing oxidative stress [45]. We described, in rats exposed to ICH, that testicles and epididymis shown an increase in lipid peroxidation markers and lower GSH levels compared with normoxic normobaric animals, and that these effects were fully reverted with concomitant administration of ascorbic acid, blueberry extracts or Ω3 chronic supplementation [44,45,46]. Indeed, these protective effects can be supported by the induction of enzymatic and non-enzymatic antioxidant defense systems.…”
Section: Reproductive Responses and Treatmentmentioning
confidence: 99%
“…Furthermore, the study avails ready information on the effects addressed in the different areas of altitude in the Kingdom of Saudi Arabia. Most investigations were carried out in high altitude laboratories or hypobaric chambers and did not simulate natural conditions (Saxena, 1995;Farias et al, 2010). The current study is again unique, as it addresses the effect of natural hypoxia on the morphology of rats exposed to natural areas of HA and then LA in the same country.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic and IHH have been associated with increased oxidative damage in the testis [6]. IHH induces high levels of lipid peroxidation, reduces glutathione reductase activity, and decreases the epididymal sperm count [7]. This environment causes more severe damage in reproductive function to immigrants than natives.…”
Section: Introductionmentioning
confidence: 99%